The associations between smartphone addiction and self-esteem, self-control, and social support among Chinese adolescents: A meta-analysis - Ding, Yueming; Wan, Xiao; Lu, Guangli; Huang, Haitao; Liang, Yipei; Yu, Jingfen; Chen, Chaoran (Frontiers in Psychology, 2022)
Background: Smartphone addiction has become a social problem that affects the healthy growth of adolescents, and it is frequently reported to be correlated with self-esteem, self-control, and social support among adolescents. Methods: A meta-analysis was conducted by searching the PubMed, Web of Science, Embase, PsycINFO, PsycArticles, China National Knowledge Infrastructure (CNKI), WANFANG DATA, and Chongqing VIP Information Co., Ltd. (VIP) databases. Stata 16.0 was used to analyse the overall effect and test the moderating effect. Results: Fifty-six studies were included, involving a total of 42,300 participants. Adolescents’ smartphone addiction had a moderately negative correlation with self-esteem (r = -0.25, 95% CI = -0.29 to -0.22, p < 0.001), a strong negative correlation with self-control (r = -0.48, 95% CI = -0.53 to -0.42, p < 0.001), and a weak negative correlation with social support (r = -0.16, 95% CI = -0.23 to -0.09, p < 0.001). Moderation analysis revealed that the correlation between adolescents’ smartphone addiction and self-esteem was strongest when smartphone addiction was measured with the Mobile Phone Addiction Tendency Scale for College Students (MPATS) (r = -0.38). The correlation between adolescents’ smartphone addiction and self-control was strongest when self-control was measured with the Middle school students’ Self-control Ability Questionnaire (MSAQ) (r = -0.62). The effect of dissertations on smartphone addiction, self-control, and social support among adolescents was significantly larger than that of journal articles. The correlation between adolescents’ smartphone addiction and social support was strongest when smartphone addiction was measured with the Mobile Phone Addiction Index (MPAI) (r = -0.24). However, the correlations between adolescents’ smartphone addiction and self-esteem, self-control, and social support were not affected by age or gender. Conclusions: There was a strong relationship between smartphone addiction and self-esteem, self-control, and social support among adolescents. In the future, longitudinal research should be carried out to better investigate the dynamic changes in the relationship between smartphone addiction and self-esteem, self-control, and social support.